Antiinflammatory and Analgesic Activities of Different Fractions of Populus tomentosa Carr. Leaves - Fu, Xueyan; Li, Tingting; Zhang, Baitong; Zhang, Xinhui; Dong, Lin; Ma, Xueqin; Chen, Jing; Qin, Luping (Asian Journal of Chemistry, 2014)
The antiinflammatory and analgesic properties of different polar fractions of Populus tomentosa leaves were investigated in mice. The analgesic activities of leaf extracts were evaluated with hot-plate and acetic acid writhing tests. Anti-inflammatory effects were studied using xylene-induced ear edema and egg albumen-induced paw edema. Low dose (1 g/kg) and high dose (3 g/kg) aqueous extracts had significant analgesic effects (p < 0.05) for the acetic acid writhing test. High doses of ethanol (3 g/kg), petroleum ether (0.5 g/kg) and butanol extracts (0.5 g/kg) prolonged hot-plate reaction times (p < 0.05) and had better analgesia. Petroleum ether extract (0.5 g/kg) was better than controls for reducing xylene-induced ear edema (p < 0.05). Low doses of aqueous (1 g/kg), ethyl acetate (0.5 g/kg) and butanol extracts (0.5 g/kg) reduced foot swelling due to egg albumen better than controls (p < 0.05). These findings indicate that water and ethanol extracts, as well as different ethanol polarity fractions, from Populus tomentosa leaves have analgesic and anti-inflammatory effects which are consistent with their use in traditional medicine.